A study of maternal outcome in heart disease in pregnancy in a tertiary care centre - Kurude, Vilas N.; Raut, Shruti U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cardiovascular disease in women is associated with 4% complications during pregnancy and is the most frequent leading cause of maternal mortality reaching up to 15%. It stands third among the most common causes of maternal mortality after obstetric haemorrhage and preeclampsia respectively.The objective of this study is to study the maternal outcome of heart disease in pregnancy. Methods: An Observational study was conducted over a period of 8 months over 50 antenatal patients with heart disease from January 2020 to August 2020 in the department of obstetrics and gynaecology, grant government medical college and JJ group of hospitals, Mumbai with appropriate inclusion and exclusion criteria. Prevalence of congenital and acquired heart disease complicating pregnancy, complications, age wise and parity wise distribution were mainly studied. Results: The incidence of heart disease was 1.8% amongst the 2,750 total deliveries conducted. In this study 46 (92%) were registered and 4 (8%) were unregistered antenatal cases. 45 (90%) belonged to upper lower class and lower class as per Kupuswamy scale with poor nutrition and antenatal care. 34 (68%) of patients had rheumatic heart disease and 11 (22%) patients had congenital heart disease. Mitral stenosis was found to be the dominant valvular lesion in rheumatic heart disease in 12 (24%) cases. Over 25 (50%) of the patients had normal vaginal delivery and 9 (18%) had instrumental vaginal deliveries, 7 (14%) with vacuum and 2 (4%) with forceps. Congestive cardiac failure was found to be the major complication found in 4 (3.9%) cases. About 8 (16%) patients required intensive care unit admission. Maternal maternity is about 4% (2 patients) in the present study. Conclusions: Maternal mortality in heart disease patients can be brought down significantly by effective preconceptional counselling, and improvements in medical, surgical, antenatal, intranatal, and postnatal care and effective motivation for contraception.